1999
DOI: 10.1128/jvi.73.10.8741-8749.1999
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Recombination among Enteroviruses

Abstract: Human enteroviruses consist of more than 60 serotypes, reflecting a wide range of evolutionary divergence. They have been genetically classified into four clusters on the basis of sequence homology in the coding region of the single-stranded RNA genome. To explore further the genetic relationships between human enteroviruses and to characterize the evolutionary mechanisms responsible for variation, previously sequenced genomes were subjected to detailed comparison. Bootstrap and genetic similarity analyses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
94
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(105 citation statements)
references
References 41 publications
11
94
0
Order By: Relevance
“…Recombination is a well-known phenomenon in enterovirus evolution. Our present findings are in line with a previous study demonstrating that several recombination breakpoints were located within the P2 and P3 regions of enteroviruses of same species, while no breakpoint was found within the P1 region by genomic analysis [30]. Other studies have also shown recombination sites located within non-structural regions, such as 2A in EV11/EV19 [24], 2B in coxsackievirus B4 [22], and 2C in echovirus 9/18 [2].…”
Section: Discussionsupporting
confidence: 92%
“…Recombination is a well-known phenomenon in enterovirus evolution. Our present findings are in line with a previous study demonstrating that several recombination breakpoints were located within the P2 and P3 regions of enteroviruses of same species, while no breakpoint was found within the P1 region by genomic analysis [30]. Other studies have also shown recombination sites located within non-structural regions, such as 2A in EV11/EV19 [24], 2B in coxsackievirus B4 [22], and 2C in echovirus 9/18 [2].…”
Section: Discussionsupporting
confidence: 92%
“…Taken together, our results suggest that in contrast to the 5=UTR, which displays a high interchangeability potential, the RV recombination possibilities at the polyprotein coding region level are more limited and viable only if involving two members of the same type or of the same species. These global findings are consistent with observations obtained from circulating RV and non-RV EV recombinants (20)(21)(22)27).…”
Section: Discussionsupporting
confidence: 91%
“…Recombination has been extensively described as an evolutionary force for both polio-and non-polio-enteroviruses (EVs) (20)(21)(22). This phenomenon is relatively rare and is mostly related to ancient events among RVs.…”
mentioning
confidence: 99%
“…In this study, genetic recombination event were found between the Fuyang HEV71 isolates, including both fatal cases and non-fatal cases, and CV-A16, which was similar to other studies [18,19]. For enteroviruses [20] and dengue viruses [21], genetic recombination is a well-known phe-nomenon and recombination could result in the emergence of viruses with altered pathogenic potentials. Except for the Fuyang HEV71 isolates, genetic recombination was also found in the HEV71 viruses, circulated in mainland of China during 1998-2008.…”
Section: Discussionsupporting
confidence: 88%